Protein product of proto-oncogene c-mil. - Patschinsky, T (1986)
Using antipeptide antibodies with specificity for the carboxyl termini of v-raf and v-mil protein products, two proteins with apparent molecular weights of approximately 71,000/73,000 and 215,000 were detected in immunoprecipitates from normal uninfected chicken cells. The 71,000/73,000-molecular-weight protein was identified as the product of the c-mil proto-oncogene by the close structural relationship of its 42,000-molecular-weight carboxyl-terminal domain to the v-mil-encoded domain of the hybrid protein p100gag-mil specified by the avian retrovirus MH2. The amino-terminal domain of the cellular protein is encoded by 5' c-mil sequences that have not been transduced into the genome of MH2. The c-mil protein (p71/73c-mil) was found to be phosphorylated in vivo, and homologous proteins were detected at variable levels in a variety of vertebrate cells, including human cells.